2014
DOI: 10.1097/pec.0000000000000211
|View full text |Cite
|
Sign up to set email alerts
|

Splenic Infarction Caused by a Rare Coinfection of Epstein-Barr Virus, Cytomegalovirus, and Mycoplasma pneumoniae

Abstract: Epstein-Barr virus (EBV), cytomegalovirus (CMV), and Mycoplasma pneumoniae are common pathogens of respiratory infection among children and young adults. Although single infection of 1 of these pathogens is common enough, their coinfection has been rarely reported. A 19-year-old woman presented with severe upper abdominal pain for 5 hours as well as flu-like symptoms and jaundice for 2 to 3 weeks. Initial tests found pancytopenia, abnormal liver functions, and presence of atypical lymphocytes in blood smear; t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 5 publications
0
10
0
Order By: Relevance
“…All cases showed improvement. Imaging was done earlier in two cases at day 7 with a CT scan, and day 10 with an MRI, respectively, showing no changes to mild aggravation in the latter [10,16]. Hence, we recommend a follow up in 4–6 weeks based on the limited follow-up imaging results.…”
Section: Discussionmentioning
confidence: 99%
“…All cases showed improvement. Imaging was done earlier in two cases at day 7 with a CT scan, and day 10 with an MRI, respectively, showing no changes to mild aggravation in the latter [10,16]. Hence, we recommend a follow up in 4–6 weeks based on the limited follow-up imaging results.…”
Section: Discussionmentioning
confidence: 99%
“…However, there were no deaths in our study, and clinical outcomes were favorable. Of the 19 patients, nine underwent follow-up imaging: CT in four cases [van Hal et al, 2005;Gang and Kim, 2013;Kobe et al, 2013;Li et al, 2014], US in three [Cull and Stein, 2012;Gavriilaki et al, 2013;Machado et al, 2015], MRI in one [Breuer et al, 2008], and one case did not mention the imaging method [Trevenzoli et al, 2001]. Seven patients showed improvement in a median follow-up time of 67 days (range, 30-128 days) [Trevenzoli et al, 2001;van Hal et al, 2005;Cull and Stein, 2012;Gang and Kim, 2013;Gavriilaki et al, 2013;Kobe et al, 2013;Machado et al, 2015].…”
Section: Discussionmentioning
confidence: 99%
“…Seven patients showed improvement in a median follow-up time of 67 days (range, 30-128 days) [Trevenzoli et al, 2001;van Hal et al, 2005;Cull and Stein, 2012;Gang and Kim, 2013;Gavriilaki et al, 2013;Kobe et al, 2013;Machado et al, 2015]. However, one patient had aggravated findings on follow-up MRI after 10 days [Breuer et al, 2008], while another patient had no change on follow-up CT performed within 7 days [Li et al, 2014]. It might be helpful to perform follow-up image examination after at least 4 weeks in order to determine the improvement in splenic infarction associated with IM.…”
Section: Discussionmentioning
confidence: 99%
“…Another study of 286 children with MPP showed that 84 (29.4%) had a mixed infection with a respiratory virus, and the highest co-detection rate was observed in young children [6]. Li et al reported a case of mixed infection with Epstein-Barr virus, cytomegalovirus, and M. pneumoniae; their case exemplifies the challenges in the diagnosis of mixed infection with multiple respiratory pathogens and the associated complications [7]. With regard to the prognosis of MPP accompanied by mixed infection, a study on adults showed that bacterial mixed infection with a respiratory virus may worsen patient outcome, including the severity and mortality of CAP [8].…”
Section: Introductionmentioning
confidence: 99%